2023
DOI: 10.3389/fonc.2023.1180988
|View full text |Cite
|
Sign up to set email alerts
|

Real world evidence of Lenvatinib + anti PD-1 as an advanced line for metastatic melanoma

Abstract: IntroductionImmunotherapy has revolutionized the prognosis of patients with metastatic melanoma. To date, the most active regimen is the combination of ipilimumab + nivolumab (ipi-nivo) achieving a response rate of nearly 60% and a median survival (OS) of 6 years. However, approximately 40% of patients experience primary resistance, while around 50% experience secondary resistance, highlighting the need for an effective second-line treatment option The recently published results on the use of lenvatinib + pemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…While these studied showed no survival benefit with Lenvatinib across all skin melanomas, it is important to highlight that acral melanomas were not considered a separate melanoma subtype in these studies. Based on a small cohort study where 4 of 6 acral melanomas responded to second-line Lenvatinib plus ICI 74 and an early clinical study where Anlotinib, another dual FGFR/VEGFR inhibitor, provided a significant survival benefit when used with ICIs 75 , targeting AM with FGFR/VEGFR inhibitors are expected to provide a survival benefit for patients. Based on these studies and our promising preclinical data, we recommend conducting a case series where patients with AM are treated with ICI and Lenvatinib, or another regionally available dual FGFR/VEGFR inhibitor, as a second- or third-line therapy to further establish clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these studied showed no survival benefit with Lenvatinib across all skin melanomas, it is important to highlight that acral melanomas were not considered a separate melanoma subtype in these studies. Based on a small cohort study where 4 of 6 acral melanomas responded to second-line Lenvatinib plus ICI 74 and an early clinical study where Anlotinib, another dual FGFR/VEGFR inhibitor, provided a significant survival benefit when used with ICIs 75 , targeting AM with FGFR/VEGFR inhibitors are expected to provide a survival benefit for patients. Based on these studies and our promising preclinical data, we recommend conducting a case series where patients with AM are treated with ICI and Lenvatinib, or another regionally available dual FGFR/VEGFR inhibitor, as a second- or third-line therapy to further establish clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The only inhibitor identified to promote stable disease or tumor regression across all AM models was Lenvatinib, a multiple receptor tyrosine kinase (RTK) inhibitor that is most potent against the VEGFR and FGFR families 20,21 . While this was a surprising finding considering the poor performance of Lenvatinib against all skin melanomas in the LEAP-003 study results (abstract O-031, 20 th Society Melanoma Research Congress 22 ), it mirrors a small study wherein six AM patients were given the drug as a second-line therapy and four patients (66%) had an objective response 23 . Mechanistically, we demonstrate that Lenvatinib has minimal direct cytotoxicity against transiently cultured AM cells and instead induces tumor regression by remodeling the tumor vasculature.…”
Section: Introductionmentioning
confidence: 93%
“…Tyrosine kinase inhibitors (TKIs), including sorafenib, lenvatinib, imatinib, sunitinib, pazopanib, and axitinib, are being evaluated in patients with AM and MM. Based on the results discussed above ( 16 , 100 , 101 , 103 , 104 , 111 ), these maybe alternative therapeutic options for patients harboring KIT mutations. Combination therapies have shown the most promise ( 124 , 125 ).…”
Section: Future Directions In Treatmentmentioning
confidence: 99%
“…The ORR and DCR was 24.1% and 82.8%, respectively ( 16 ). A real-world study found a response rate (RR) of 28%, DCR of 38%, median PFS of 3 months, and median survival of 11 months with lenvatinib and pembrolizumab in advanced metastatic melanoma, including 6 MM and 4 AM ( 104 ).…”
Section: Systemic Treatmentmentioning
confidence: 99%